ARTIFICIAL INTELLIGENCE REPLACES HUMAN TRANSLATORS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper explores the growing influence of artificial intelligence (AI) technologies, particularly ChatGPT, DeepL, and similar systems, in the field of translation. With AI transforming traditional translation processes, a critical question arises: can AI replace human translators? The article examines the distinctions between human and machine translation, potential for collaboration, and the inherent limitations of AI systems. The author emphasizes the importance of human cognition, cultural sensitivity, and contextual awareness in translation, ultimately arguing for a future where AI serves as an aid rather than a substitute for human translators.